Ogólna charakterystyka międzynarodowego prawa ochrony środowiska - Rosicki, Remigiusz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The paper provides a synthetic grasp of the issues related to international environmental law. It should be emphasized that the paper offers only a general review of this law. The significant issues the paper touches upon concern the processes and directions of international environmental law development. Besides, the following categories are analyzed: the environment, environmental protection, the sources of international environmental law, and its principles. The paper also includes an analysis of the fundamental documents that include the principles of international environmental law (in particular the sustained development principles), inter alia the Stockholm Declaration and the Rio de Janeiro Declaration.